Production of bioethanol from coconut (Cocos nucifera) husk by enzymatic hydrolysis using Aspergillus niger / Anis Athirah Bahri - Bahri, Anis Athirah (2016)
Coconut (Cocos nucifera) husk were abundant in Malaysia and it was employed as raw material in production of bioethanol. The conventional ethanol from petroleum-based would cause environmental hazard and it was known as nonrenewable resource. The objectives of this study to synthesis bioethanol from coconut husk, to determine the ability of Aspergillus niger in hydrolysis of cellulose into glucose and to determine the optimum temperature for fermentation process. There were four steps that should be followed sequentially in order for bioethanol production; there were pretreatment, enzymatic hydrolysis, fermentation and distillation. Within seven days of hydrolysis process, the result showed that, the reducing sugar production was increased from 0.01 mg.ml-l to 1.60 mg.ml-l . The temperature for fermentation process was manipulated into three different temperatures, 26°C, 30°C and 34°C. Among those three (3) temperatures, 26°C showed the highest concentration of bioethanol, 0.27%. Bioethanol from coconut husk showed peak at 3434.06 nm. It indicated the presence of of hydroxyl group (OH) which was the properties of ethanol. As a conclusion, Aspergillus niger had the ability to hydrolyse cellulose into monomeric sugar and 26°C was determined as the optimum temperature for the fermentation process.